How do you simplify #(k^4m^3p^2)/(k^2m^2)#?

1 Answer
May 19, 2017

Answer:

See a solution process below:

Explanation:

First, rewrite this expression as:

#(k^4/k^2)(m^3/m^2)p^2#

Next, use this rule of exponents to simplify the #k# and #m# terms:

#x^color(red)(a)/x^color(blue)(b) = x^(color(red)(a)-color(blue)(b))#

#(k^color(red)(4)/k^color(blue)(2))(m^color(red)(3)/m^color(blue)(2))p^2 => k^(color(red)(4)-color(blue)(2))m^(color(red)(3)-color(blue)(2))p^2 => k^2m^1p^2#

Now, use this rule of exponents to further simplify the #m# term:

#a^color(red)(1) = a#

#k^2m^color(red)(1)p^2 = k^2mp^2#